ANALISIS KUALITAS AIR SUMUR UNTUK EKSTRAKSI PATI SAGU - Nururrahmah Hammado; Nurmalasari; Laurensius Leong Liwu; Sukarti (Cokroaminoto Journal of Chemical Science, 2023)
The main process in processing sago to obtain sago starch uses large amounts of water. One of the factors that determine the quality of sago starch is the water used for sago starch extraction because water is used to separate sago starch from sago fiber. The purpose of this study was to determine the quality of ground water used for sago starch extraction based on physical and chemical parameters. The physical parameters analyzed were the temperature, turbidity, odor, taste, and color of the ground water, while the chemical parameters analyzed were the concentrations of BOD, COD, Fe, and the pH of the ground water. Water samples were obtained from wells in Jaya Village, Telluwanua District, Palopo City. The preparation and testing of water quality were carried out at the Natural Materials Laboratory of the Faculty of Science, University of Cokroaminoto Palopo, and the Chemical Laboratory of the Makassar City Environmental Service. The results showed that the quality of ground water was based on physical parameters: temperature (26 oC), turbidity 7.54 NTU, ground water was odorless, tasteless, and colorless, while chemical parameters obtained BOD concentration of 2.2 mg/L; COD was 27.3 mg/L, and Fe metal was 4 mg/L. The results indicate that the ground water used for sago starch extraction is still within the threshold required for water quality (Class II). This research can be continued by adding tests for biological parameters, as well as several other parameters such as TDS, hardness, and several other hazardous metals so that the results of this study can be used as consideration for using the ground water as a source of water for sago starch extraction.